Diagnostic and therapeutic strategies for non-alcoholic fatty liver disease - Fu, Yajie; Zhou, Yanzhi; Shen, Linhu; Li, Xuewen; Zhang, Haorui; Cui, Yeqi; Zhang, Ke; Li, Weiguo; Chen, Wei-dong; Zhao, Shizhen; Li, Yunfu; Ye, Wenling (Frontiers in Pharmacology, 2022)
The global incidence rate of non-alcoholic fatty liver disease (NAFLD) is approximately 25%. With the globalization of obesity and its associated metabolic syndromes, NAFLD has become an important cause of chronic liver disease in many countries. Despite recent advances in pathogenesis, diagnosis, and therapeutics, there are still challenges in treating the disease. In this review, we briefly described diagnostic methods, therapeutic targets, and drugs related to NAFLD. In particular, we focused on evaluating carbohydrate and lipid metabolism, lipotoxicity, cell death, inflammation, and fibrosis as potential therapeutic targets for NAFLD. We also summarized the clinical research progress in drug development and combination therapy, hoping to provide references for NAFLD drug development.